Autologous blood products and their role within dentistry. (2nd July 2019) - Razzak, Arif; Jenkins, Sarah; Smart, Keith
Abstract : Use of autologous blood products, such as platelet rich plasma (PRP) and platelet rich fibrin (PRF) is increasing within the field of dentistry. Such products aim to promote bone regeneration which is valuable in a range of procedures, including implant placement, post tooth extraction, and periodontal surgery. Dental practitioners should be aware of what these new materials are, and the beneficial role that they may play in modern dentistry. CPD/Clinical Relevance: This article aims to inform the reader regarding the range of available autologous blood products, their uses in dentistry, how they are derived from whole blood, as well as cost and time implications.